Primary maternal cytomegalovirus infections during pregnancy: association of CMV hyperimmune globulin with gestational age at birth and birth weight. (January 2015) - Nigro, Giovanni; Capretti, Ilaria; Manganello, Anne-Marie; Best, Al M.; Adler, Stuart P.
Abstract Background: Cytomegalovirus (CMV) hyperimmune globulin (HIG) may be helpful after a primary maternal CMV infection during pregnancy as a therapy for infected fetuses or to prevent maternal-to-fetus transmission of CMV. Although immunoglobulins administered during pregnancy appear safe, previous studies have not monitored HIG for a possible effect on duration of gestation and birth weight. Methods: We used clinical data on 358 women with a primary CMV infection during pregnancy, 164 of whom received one or more infusions of HIG. Results: The average birth weight of the 358 infants was 3076 g and the average gestational age at delivery for 351 women was 38.2 weeks. After adjusting for potential confounding variables, the only factor associated with low birth weight and the duration of gestation was the presence of symptoms at birth. The receipt of HIG was not associated with either a diminished birth weight or a reduced duration of pregnancy. The receipt of multiple doses of HIG (range 1–8) was significantly correlated with an increase in birth weight (p = 0.006) and gestational age at delivery (p = 0.014). This correlation was also significant for all asymptomatic infants and for infants whose mothers received multiple doses of HIG to prevent fetal infection. Conclusion: HIG administration during pregnancy is not associated with either diminished gestation or decreased birth weight and may enhance these parameters among women who receive multiple doses starting in early gestation.